Implementation of photovoltaic and simple resonant power converter for high frequency discharge application - Facta, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Ozone gas (O3) is widely used in deodorization, decolourization, disinfection, bleaching processes, gas/air treatment, chemical synthesis and recently in medical applications. Due the wide application of ozone then the ozone generator or ozonizer is urgently needed. A single switch resonant converter with ferrite transformer is proposed in this work. The prototype is constructed by two parts, first is ozone chamber and the second part is power converter with a single switch resonant converter and it supplied by photovoltaic simulator. The converter is successful to convert 12 volt from photovoltaic to 1.89 kVpp high frequency voltage to ozone chamber. The ozone gas produce with the proposed system is 450 ppm with oxygen as an input gas.